Pengaruh Lama Waktu Fermentasi Terhadap Kadar Bioetanol dari Pati Ubi Jalar Kuning (Ipomea batata L) - Moede, Fika Herlina; Gonggo, Siang Tandi; Ratman, Ratman (Jurnal Akademika Kimia, 2017)
The sweet potato is yellow is one that the carbohydrate that is high, so it can be used as one of the alternative raw materials for bioethanol. This study aims to determine the levels of ethanol sweet potato is yellow through fermentation with the use of yeast bread with a variety of time 3, 4, 5, 6, dan 7 days at room temperature. The results of the research showed glucose levels derived from the process of hydrolysis using acid HCl 21% were of 4.54% with high levels ethanol that optimum obtained through fermentation use of yeast Saccharomyces cerevisiae of 9.70% over fermentation 5 days.